Pre-implant evaluation of quantity and quality of mandibular bone in male diabetes mellitus patients using cone-beam computed tomography: A case-control study - Anuja Kammari; Komali Garlapati; K Ajaykartik; Ancy V Ignatius; B Elizabeth Surekha; Asra Saba (Wolters Kluwer Medknow Publications, 2022)
Objectives: This study was designed to evaluate and compare the quantity and quality of mandibular bone in the first molar region in male type 2 diabetes mellitus (T2DM) patients with healthy controls using cone-beam computed tomography (CBCT) imaging technique. The bone characteristics in T2DM patients were correlated with diabetes duration. Materials and Methods: The study included 25 male diabetic patients and 25 nondiabetic male patients with missing mandibular 1st molar, in the age group ranging from 35 to 60 years. HDX WILL CBCT machine utilized to obtain CBCT images. Bone density and quantitative linear measurements were performed in OnDemand software, along with glycated hemoglobin levels of diabetic patients. The obtained data were subjected to statistical analysis using the SPSS software version 20.0. Results: Type 2 diabetic patients had greater bone density as compared to controls. The height of bone is less in diabetic patients than in nondiabetics, and other quantitative linear measurements were found similar in both groups. Conclusion: This study concluded that CBCT can be used in preimplant planning and helps the clinician assess bone measurements and bone density.